The experiences of bidayuh in the development of native customary rights land in Singai / John Jussem ... [et al.] - Jussem, John; Madi, Nero; Atan, Patrick (2012)
Native customary rights to land issues are normally controversial. Tensions exist when the State, in pursuit of development, and the natives both claim, among others, ownership of the land. Ngidang (2005) identifies colonial legacy as one of the issues. Perera (2009) argues method of development, while Bulan (2009) elucidates human rights violations. In various parts of Sarawak, some of the tensions manifest themselves in Court cases filed by the natives against either the State government and commercial logging or palm oil companies. In essence, Ngidang, Perera and Bulan argue that present land tenure system is not working. Not all the natives in Sarawak share and experience the state of heightened tension between the development stakeholders. In Singai, Bau district, the Singai natives are able to maintain their natives customary rights to land in the face of development. The study covers the area of Singai in Bau, Sarawak.